China's Domestic Transformation in a Global Context - Song, Ligang; Garnaut, Ross; Fang, Cai; Johnston, Lauren (ANU Press, 2015)
The phrase 'New Normal' captures the ongoing shift in the pattern and drivers of China's economic growth. China's new growth rate is both slower and imposing difficult structural change. These new economic conditions are challenging yet offer opportunities for China and its economic partners. Reforms must be deepened but also make growth more inclusive and environmentally sustainable, over this decade and beyond. This year's Update offers both global context and domestic insight into this challenging new phase of China's domestic economic transformation. How are policymakers elevating migrant workers concurrent with increasing consumption? Is China's government spending enough on education and R&D to ensure it can achieve its aspirations to ascend the global manufacturing value chain and avoid the middle-income trap? Are energy market reforms reducing or increasing the price of gas and electricity in China? What are the consequences of China's financial reforms and expanding Renminbi trading for foreign banks? What does China's new growth model mean for the international resources economy and for Africa? Do SOEs face market conditions and are they dominating China's fast-rising outbound investment? What is China's strategy for navigating fragmented international trade policy negotiations?